Differences of oral health knowledge, attitude, and practice among orphan residents: a cross-sectional study - Ibrahim, Sukaeni; Ibrahim, Juliani; Hardjo, Marhaen; Wahyudin, Bob; Abrar, Hanan Khasyrawi; Maningo Rodis, Omar Marianito (Universitas Padjadjaran, 2026)
Introduction: Oral health is essential to the general health and well-being of all children and adults. The implementation of oral health behaviour is expected to start at an early age in the family environment, although the orphaned are often neglected. This study aimed to analyze differences of oral health knowledge, attitude, and practice differences of oral health knowledge, attitude, and practice among orphan residents. Methods: This analytical study used a cross-sectional method, comprising 346 orphaned residents from 27 orphanages in Makassar City. A total of 24 items; a closed-ended structured questionnaire was used to assess oral health knowledge, attitude, and practice among orphans. Furthermore, a stratified random sampling method was used for sample selection. Data analysis was conducted with the Mann-Whitney U statistical test. Results: The results showed that 65% of orphan residents had sufficient knowledge, 80% possessed a good attitude, and 53.8% had sufficient behaviours regarding oral health. Significant differences were observed in oral health knowledge, attitude, and practice based on age groups (p<0.05). Notably, there were also significant differences in knowledge and attitude (p<0.05) related to oral health among orphan residents. Conclusion: There were differences in knowledge and practices, and generally good attitudes towards oral health. Moreover, orphanage caretakers should be educated and trained in oral health practice.